Dimorphism of right–left asymmetry in the female genitalia of the brachypterous grasshopper Parapodisma mikado (Orthoptera: Acrididae). Issue 4 (1st July 2016) - Shimizu, Daisuke; Sugano, Yoshikazu C.; Tsuchiya‐Suzuki, Kaori; Ito, Gen; Akimoto, Shin‐ichi
Abstract: Several insects exhibit morphological asymmetry in the mouthparts or genitalia. In a part of species with asymmetric genitalia, two mirror‐image forms of the genitalia are reported to occur in a population. This dimorphism, called chiral dimorphism, is usually observed in male genitalia, but its examples in female genitalia are very limited. Here, we report that the females of the brachypterous grasshopper Parapodisma mikado are equipped with an asymmetric sclerite in the copulatory bursa, and that two mirror‐image forms of the sclerite occur in local populations. This dimorphism was detected in all of seven populations examined, and the ratio of the two forms was approximately 2:1 for the right : left forms. In one population, the ratio of the two forms did not vary among three consecutive years. Thus, chiral dimorphism in the female genitalia is kept almost constant spatiotemporally. Mating experiments indicated that the direction of female genitalia did not affect the direction to which the males twist their abdomen (right or left side) during mating or the duration of mating. We propose two hypotheses, a neutral developmental mechanism and sexual conflict, for the maintenance of chiral dimorphism in the genitalia of P. mikado females. Abstract : We found antisymmetric female genitalia in a brachypterous grasshopper. The dimorphism is broadly and continually maintained at certain ratio. We researched how this phenomenon has been endured among the species.